Building Information Bridges Between Parents and Health Care Providers in the Neonatal Intensive Care Unit - Helliwell, Michelle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The goal of this study was to investigate the information needs of parents in a neonatal intensive care unit environment (NICU), and to uncover any gaps in the information exchange between parents and health care providers as perceived by parents of NICU patients. Brenda Dervin's sense-making theory was employed to test the idea that health care providers (HCPs) offered information . . .